Research on construction management based on BIM-AR/VR technology - Ma Songke (E3S Web of Conferences)
With the digital transformation of the construction industry, construction management built by BIM and AR/VR technologies has gradually become a crucial mean to enhance efficiency, reduce costs and promote environmental protection. This paper discusses the application of BIM combined with AR/VR in construction management, and demonstrates its advantages in project visualisation, collaborative communication and safety management through literature analysis. The combined technology can significantly improve the transparency and precision of project management, help managers better control construction progress and costs, optimise resource allocation, and reduce rework. At the same time, the introduction of AR/VR improves worker training, decreases the risk of accidents and promotes the intelligent and green development of construction management. Although the technology still faces problems such as data compatibility, applying BIM and AR/VR in construction management is promising with the integration of new technologies such as artificial intelligence.